Dirección por valores y responsabilidad social empresarial en la Cooperativa de Ahorro y Crédito Nuestra Señora del Rosario, Agencia Huamachuco, año 2015. - Martinez Martell, Liz Isaura (2015)
This thesis has taken place in the city of Huamachuco, La Libertad, Peru; Its main objective substantiate how the Department contributes Securities Corporate Social Responsibility in the entity under study. After reviewing the issue really it has formulated the research question: How Management by Values contributes to Corporate Social Responsibility in the credit union Nuestra Señora del Rosario, Huamachuco Agency, 2015?. For the gathering of data has been looked at two populations: 29 8348 workers and union members; of them they have obtained samples of 29 workers and 94 partners respectively. It has been revised official documentation of the entity and surveys have been applied to the indicated samples. With the results, and following the scientific method it has made the corresponding analysis and discussion, leading to demonstrate the validity of the hypothesis which states that: “Management by Values contributes positively to Corporate Social Responsibility in the Credit Union Credit Nuestra Señora del Rosario, Huamachuco Agency, 2015 ". Finally the formulation of conclusions and recommendations, you have to: the main conclusion states that specifically factors CSR: the institutional philosophy, respect for human rights and the fight against corruption, are influenced by "all" Address factors Securities; meanwhile CSR in everyday practice is influenced by the commitment to cooperative principles and values, and the action of cooperative education. The main recommendation states that it is essential to strengthen policies and practices in cooperative entities, based on the principles and values of international cooperative; and in particular how the cooperative study should establish networks with other cooperatives in the world to facilitate technical and financial assistance; various campaigns campaigns outreach to the community such as: health and sanitation, quality education, crime and drug addiction, and rational use of water and energy; also the partners must fulfill their credit obligations with suppliers and paying taxes, and trabajares fulfill their duties of office.